2023
DOI: 10.1007/s11325-023-02799-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous positive airway pressure and mandibular advancement appliance therapy on sleep bruxism in adults with obstructive sleep apnea: a pilot study

Abstract: Study objectives This study aimed to investigate the effects of continuous positive airway pressure (CPAP) and mandibular advancement appliance (MAA) therapy on rhythmic masticatory muscle activity (RMMA), a biomarker of sleep bruxism (SB), and to compare the effects of CPAP with MAA in adults with obstructive sleep apnea (OSA). Methods This cohort study included individuals with OSA who received treatment with CPAP or MAA. Polysomnographic recordings with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A recent study on OSA concomitant with SB showed that CPAP was as effective as MAD in reducing bruxism and more effective in reducing respiratory events. 7 Our cases confirm that CPAP therapy could be an essential treatment option for patients with SB and OSA, especially when the effect of oral appliance therapy is inadequate. In addition, the common craniofacial features among our patients, such as dolichocephalic face and a high palate, suggest that CPAP could be effective, especially in patients with these craniofacial features.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…A recent study on OSA concomitant with SB showed that CPAP was as effective as MAD in reducing bruxism and more effective in reducing respiratory events. 7 Our cases confirm that CPAP therapy could be an essential treatment option for patients with SB and OSA, especially when the effect of oral appliance therapy is inadequate. In addition, the common craniofacial features among our patients, such as dolichocephalic face and a high palate, suggest that CPAP could be effective, especially in patients with these craniofacial features.…”
Section: Discussionsupporting
confidence: 71%
“…A recent study suggested that PSG with the bilateral temporalis or masseter muscles, or both, is valid for SB recording. 7 Although SB was not confirmed by PSG in Case 3, he had a clear history of SB and reported clinical improvement of SB and related jaw pain by CPAP, suggesting that CPAP can also be used as an alternative even in probable SB, which has not been proven in PSG.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation